Innovación de productos turísticos de la comunidad Santa Teresita en el cantón Sucúa, provincia de Morona Santiago - Solis Garzón, Stefanny Marcela (2026)
The objective of this study was to analyze the creation of innovative tourism products as a strategy to strengthen community tourism and cultural preservation in the Santa Teresita Community, Sucúa Canton, Morona Santiago Province. Given the characteristics of the study, a qualitative, descriptive methodology was used. Data was collected through surveys of community leaders, community residents, and even tourists. A set of descriptive statistical techniques was used to analyze the data, which helped to identify the current conditions of promotion, infrastructure, and active community participation. The results obtained show that the community has great cultural and natural potential, but also reveal limitations in tourism marketing and promotion. The implementation of these innovative tourism products will help strengthen community tourism and sustainable development in the community of Santa Teresita.